Exercise enjoyment does not predict change in maximal aerobic power during a strenuous 10-week endurance exercise intervention - Matomäki Pekka; Heinonen Olli J.; Nummela Ari; Kokkonen Marja; Kyröläinen Heikki (Sciendo, 2024)
Study aim: Although exercise enjoyment is well studied in behavioral context, its associations to aerobic fitness adaptations during exercise interventions have received less attention.